Variants in GATA4 Are a Rare Cause of Familial and Sporadic Congenital Diaphragmatic Hernia - Yu, Lan (2012)
Congenital diaphragmatic hernia (CDH) is characterized by incomplete formation of the diaphragm, occurring as either an isolated defect or in association with other anomalies. Genetic factors including aneuploidies and copy number variants are important in the pathogenesis of many cases of CDH, but few single genes have been definitively implicated in human CDH. In this study, we used whole exome sequencing (WES) to identify a paternally inherited novel missense GATA4 variant (c. 754C>T, p. R252W) in a familial case of CDH with incomplete penetrance. Phenotypic characterization of the family included magnetic resonance imaging (MRI) of the chest and abdomen demonstrating asymptomatic defects in the diaphragm in the two “unaffected” missense variant carriers. Screening 96 additional CDH patients identified a de novo heterozygous GATA4 variant (c.848G>A; p.R283H) in a non-isolated CDH patient. In summary, GATA4 is implicated in both familial and sporadic CDH, and our data suggests that WES may be a powerful tool to discover rare variants for CDH.